Use of High dose Corticosteroids Reversed COVID-19 Associated ARDS in a Patient Listed for Lung Transplantation - Erp, JM Kwakkel-van; Dams, K; Verplancke, V; Raman, P; Ruttens, D; Thiessen, SE; Baar, I; Jacobs, R; Lauwers, P; Yogeswaran, K; Verleden, SE; Hendriks, JMH (Archives of Clinical and Medical Case Reports, 2022)
Patients with COVID-19 associated ARDS have a mortality rate varying from 30-60%. If there is mono-organ failure and recovery is deemed unlikely despite optimal care, these patients are eligible for lung transplantation. We present our experience with high dose corticosteroid pulse therapy in an ICU patient on ECMO and mechanical ventilation, listed for lung transplantation. The patient responded with improved oxygenation, was weaned from ECMO and delisted from lung transplant waiting list.